Modelling of the process of heating glass Fabric - Buikis, A.; Ulanova, N. (Mathematical Modelling and Analysis, 1996)
“Modelling of the process of heating glass Fabric” Mathematical Modelling Analysis, 1(1), p. 16-20. First Published Online: 14 Oct 2010